2012
DOI: 10.4067/s0716-97602012000300004
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog in cancer stem cells: a novel link with autophagy

Abstract: The Sonic Hegdehog/GLI (SHH/GLI) pathway has been extensively studied for its role in developmental and cancer biology. During early embryonic development the SHH pathway is involved mainly in pattern formation, while in latter stages its function in stem cell and progenitor proliferation becomes increasingly relevant. During postnatal development and in adult tissues, SHH/GLI promotes cell homeostasis by actively regulating gene transcription, recapitulating the function observed during normal tissue growth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 69 publications
1
44
0
Order By: Relevance
“…41 It had been reported that the Hh signaling pathway regulates autophagy. 42, 43, 44 Jimenez-Sanchez et al 42 have confirmed that Gli2 is necessary for the inhibition of autophagy by Hh signal, but they were unable to completely exclude the contribution of Gli1 and Gli3 to autophagy regulation. The mechanism by which Gli1 regulates autophagy is still unclear and the role of autophagy in cell growth and cell death in chondrosarcoma is still being debated considerably.…”
Section: Discussionmentioning
confidence: 99%
“…41 It had been reported that the Hh signaling pathway regulates autophagy. 42, 43, 44 Jimenez-Sanchez et al 42 have confirmed that Gli2 is necessary for the inhibition of autophagy by Hh signal, but they were unable to completely exclude the contribution of Gli1 and Gli3 to autophagy regulation. The mechanism by which Gli1 regulates autophagy is still unclear and the role of autophagy in cell growth and cell death in chondrosarcoma is still being debated considerably.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that aggressive breast tumors often enriched in CSCs [33, 50, 57], exhibit moderate to strong nuclear positivity for TRIM28 and TRIM28-S824-phospho protein more frequently than luminal A tumors, considered to be more differentiated and nonaggressive (Figure 1D). Although these results are not statistically significant, probably due to small number of tested samples, they are consistent with previous reports [22, 23], (see also Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Shh acts as a classical morphogen during embryonic development, regulating the pattern of formation in the nervous, respiratory, and intestinal systems34353637. Postnatally, Shh pathways regulate tumorigenesis by controlling gene transcription and autophagy to maintain normal cell homeostasis3839. Shh signaling activity is governed by the balance of Gli activators and repressors40.…”
Section: Discussionmentioning
confidence: 99%